2013
DOI: 10.1242/jcs.124784
|View full text |Cite
|
Sign up to set email alerts
|

A ligand-specific kinetic switch regulates glucocorticoid receptor trafficking and function

Abstract: SummaryThe ubiquitously expressed glucocorticoid receptor (GR) is a major drug target for inflammatory disease, but issues of specificity and target tissue sensitivity remain. We now identify high potency, non-steroidal GR ligands, GSK47867A and GSK47869A, which induce a novel conformation of the GR ligand-binding domain (LBD) and augment the efficacy of cellular action. Despite their high potency, GSK47867A and GSK47869A both induce surprisingly slow GR nuclear translocation, followed by prolonged nuclear GR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Each of these 'peripheral' clocks can track light and dark through messages received from the 'central clock' or pacemaker in the suprachiasmatic nucleus of the brain. The central pacemaker integrates light and dark information and relays the information downstream by a network involving neural pathways, hormone release (glucocorticoids), and metabolic cues from rhythmic feeding behavior [8,9]. Light is the key entrainment factor for the SCN and feedingregulated metabolic cues are pivotal for the regulation of many peripheral clocks [8,9] Both central and peripheral clocks use the same molecular machinery to ''time'' the day.…”
Section: How Are Circadian Rhythms Regulated?mentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these 'peripheral' clocks can track light and dark through messages received from the 'central clock' or pacemaker in the suprachiasmatic nucleus of the brain. The central pacemaker integrates light and dark information and relays the information downstream by a network involving neural pathways, hormone release (glucocorticoids), and metabolic cues from rhythmic feeding behavior [8,9]. Light is the key entrainment factor for the SCN and feedingregulated metabolic cues are pivotal for the regulation of many peripheral clocks [8,9] Both central and peripheral clocks use the same molecular machinery to ''time'' the day.…”
Section: How Are Circadian Rhythms Regulated?mentioning
confidence: 99%
“…The central pacemaker integrates light and dark information and relays the information downstream by a network involving neural pathways, hormone release (glucocorticoids), and metabolic cues from rhythmic feeding behavior [8,9]. Light is the key entrainment factor for the SCN and feedingregulated metabolic cues are pivotal for the regulation of many peripheral clocks [8,9] Both central and peripheral clocks use the same molecular machinery to ''time'' the day. Interlocking repressing and activating transcriptional and translational feedback loops culminate in the approximately 24-h rhythmic expression and activity of a set of core clock genes in each organ.…”
Section: How Are Circadian Rhythms Regulated?mentioning
confidence: 99%
“…Although the conformational states of unliganded steroid receptor proteins remain poorly characterized, crystal structures of various ligand-bound states demonstrate that the conformational transitions of the ligand binding domain which are induced by steroid antagonists generally differ from those induced by steroid agonists, and these distinct conformations can differentially interact with co-regulators (17). In addition, a concurrent conformational transition in the Hsp90 subunits has been proposed to serve as a component of a larger scale allosteric response (18).…”
mentioning
confidence: 99%
“…It should be noted that basal NIK stability has been observed in primary human cells indicating that not all signaling within this pathway may solely depend on receptor stimulation (Razani et al, 2011). It was also demonstrated that conformational changes induced by novel glucocorticoid receptor (GR) ligands can mediate new mechanisms of GR regulation (Trebble et al, 2013). Mapracorat is a ligand for GRs (Schacke et al, 2007) and may trigger conformation changes that enable rapid activation, leading to changes in transcriptional activity, or recruitment or replacement of accessory proteins that govern GR signaling outcomes.…”
Section: Discussionmentioning
confidence: 99%